2013
DOI: 10.1016/j.ijgo.2012.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Simplified medical abortion using a semi-quantitative pregnancy test for home-based follow-up

Abstract: Objective: To simplify follow-up after medical abortion by examining whether women could use a semiquantitative pregnancy test at home to screen for ongoing pregnancy. Methods: Three hundred women seeking medical abortion at a tertiary hospital in Vietnam participated in the study. Participants used a semiquantitative pregnancy test at the hospital to estimate baseline human chorionic gonadotropin (hCG) levels and administered another test at home 2 weeks later for comparison. Women interpreted the test result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…Although ongoing pregnancy occurs <1% of the time with mifepristone and misoprostol ≤10 weeks of gestation, there is ongoing investigation into how best to identify these women, whether it be symptom‐based or by use of semi‐quantitative4, 31, 32 or low‐sensitivity2, 3 urine pregnancy tests. The critical step for safely self‐using medical termination is understanding when to seek medical care, both for signs and symptoms of ongoing pregnancy as well as for complications such as bleeding and infection, and documenting that they are able to do so.…”
Section: Discussionmentioning
confidence: 99%
“…Although ongoing pregnancy occurs <1% of the time with mifepristone and misoprostol ≤10 weeks of gestation, there is ongoing investigation into how best to identify these women, whether it be symptom‐based or by use of semi‐quantitative4, 31, 32 or low‐sensitivity2, 3 urine pregnancy tests. The critical step for safely self‐using medical termination is understanding when to seek medical care, both for signs and symptoms of ongoing pregnancy as well as for complications such as bleeding and infection, and documenting that they are able to do so.…”
Section: Discussionmentioning
confidence: 99%
“…12 Recent research suggests that a set of questions or a symptom checklist combined with an appropriate pregnancy test may be the best strategy for out-of-clinic self-assessment of abortion outcome. 7,16,19,20 For out-of-clinic self-assessment the importance of timely identification of ongoing pregnancies is obvious. In the South African public sector, second trimester abortion services are only available in a small number of secondary and tertiary hospitals and the services are overbooked and difficult for women to access.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies have shown that as medical abortion with mifepristone and misoprostol becomes better known and is further demedicalized,* women increasingly don't return to the clinic if they consider the procedure to have been complete. 7,8 Tracing women by telephone who have not returned for follow-up, in order to reassure providers that treatment has been successful, can be time consuming 9 and may not be feasible in resource-constrained settings like the South African public sector (Personal communication, regional health manager, 2010).…”
mentioning
confidence: 99%
See 2 more Smart Citations